The archaeology of persistent places: the Palaeolithic case of La Cotte de St Brelade, Jersey. (21st November 2016) - Shaw, Andrew; Bates, Martin; Conneller, Chantal; Gamble, Clive; Julien, Marie-Anne; McNabb, John; Pope, Matt; Scott, Beccy
Abstract: Abstract : Excavations at the Middle Pleistocene site of La Cotte de St Brelade, on the island of Jersey in the English Channel, have revealed a long sequence of occupation. The continued use of the site by Neanderthals throughout an extended period of changing climate and environment reveals how, despite changes in the types of behaviour recorded at the site, La Cotte emerged as a persistent place in the memory and landscape of its early hominin inhabitants. The site's status as a persistent place for these people suggests a level of social and cognitive development permitting reference to and knowledge of places distant in time and space as long ago as at least MIS 7.